INFLUENCE OF EXPLICIT INSTRUCTION METHODS ON THE ABILITY TO READING COMPREHENSION GRADE V - Kiki Febrina (Education Generation Journal, 2022)
This study aims to determine the ability to read comprehension before and after by applying the Explicit Instruction Method. This type of research is a Pre-Experiment type of Design One Group Pretest-Posttest Design, which is an experiment carried out on only one group, without any comparison. This research was conducted at SD Negeri 006 Baturijal Barat class V which totaled 24 students. Based on the results of the study, it was obtained that the average test score of learning outcomes before treatment (pretest) was 49.58 while the average test score of learning outcomes after treatment (posttest) was 73.33 and the average gain value was 0.48 which is a moderate interpretation, as well as hypothesis test results using a t-test with t-test with tcount = 15.117 and ttable = 1.714 then it was concluded tcount > ttable, then reject Ho means significant. This means that there is an influence on the ability to read comprehension of grade V students of SD Negeri 006 Baturijal Barat between before (pretest) and after (posttest) by applying the Explicit Instruction Method. This shows that the Explicit Instruction Method affects the reading comprehension ability of grade V students of SD Negeri 006 Baturijal Barat.